Integrasi Analisis Preferensi Visual dan Bahaya Lanskap dalam Perencanaan Wisata di Taman Hutan Raya Ir. H. Djuanda, Bandung - Fitri Rahmafitria; Purna Hindayani (http://arl.faperta.ipb.ac.id/, 2022)
Ir. H. Djuanda Forest Park, is a natural tourism destination located in Bandung, West Java and in low land parts of Gunung Pulosari, passed by Cikapundung river stream. This research aimed to recommend the appropriate tourism planning to be implemented in the Ir. H. Djuanda Forest Park. Through landscape hazard analysis within slope gradient and soil element contained, we developed landscape sensitivity map. The result shows that 65,508% from the total area is a high sensitivity land. Beside that, only 4,335% from the total area is a low sensitivity lands and can be explored for active tourism attraction. The visual preference analysis was held to identify the potential attractiveness of many tourisms object in this area. The high potential object is dominanated with natural landscape objects and man-made object is the less potential. Almost all of the potential objects are located in high sensitivity land. Unfortunately, the uninterested object with unclear function is located in low sensitivity land which it is suitable for intensive recreation activities. The planner of this area should consider the role of limited activities and facilities development in low caring capacity land. For conservation purpose, planting endemic vegetation in sensitive landslide land should be carried out in order to maintain forest sustainability.